What You Need to Apply for Disaster Rehabilitation Assistance - Regina Fegan; Michael T. Olexa (EDIS)
After a disaster, you may need to seek financial assistance to restore your home or farm. There are many sources of assistance, but you will be required to provide certain information. The lists in this publication can help you assemble the necessary information before you meet with any agents.  This document, IFAS publication DH0438, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.